Plantas Tóxicas de interesse pecuário provocam sérios prejuízos aos produtores em todo o mundo. No Brasil essas plantas também causam prejuízos relevantes aos pecuaristas. - Geraldo Neto, Severino Antonio (Universidade Federal Rural do Semi-Árido, 2012)
Its economic importance is due to the death of animals, decreased production and high cost control measures and prophylaxis. and lack of data on the frequency of animals mortality by regions, has hindered define the economic impact that these have been causing in the country. Therefore, this work aimed to determine the poisonous plants species and the poisonings promoted by them in 35 cities from Central and West regions of Rio Grande do Norte state, Brazil. The study was conducted at micro-regions of Macau, Angicos and Serra de Santana from Central region, constituted by 20 cities; and at micro-regions of Mossoró and Vale do Assú from West region, constituted by 15 cities. It were visited all the cities, and veterinarians, agronomists, agriculture experts and farmers were interviewed using three forms. Data obtained in the interviews were compiled and analyzed using the software Epi Info version 6.04. From the 217 interviews done in this study, it was reported 1,483 outbreaks of poisoning by plants with proven toxicity. The plant species responsible by greater number of poisoning outbreaks were Ipomoea asarifolia (308 outbreaks), Aspidosperma pyrifolium (285 outbreaks), Indigofera suffruticosa (189 outbreaks), Manihot carthaginensis subsp. glaziovii (153 outbreaks), and Amorimia rigida (87 outbreaks). The other plant species with proven toxicity pointed as responsible by poisonings were Anadenanthera colubrina var. cebil, Cnidoscolus quercifolius, Crotalaria retusa, Froelichia humboldtiana, Ipomoea carnea, Leucaena leucocephala, Marsdenia megalantha, Manihot esculenta, Mimosa tenuiflora, Nerium oleander, Plumbago scandens, Prosopis juliflora, Ricinus communis, Sorghum bicolor, Sorghum halepense, Tephrosia cinerea , and Urochloa (Brachiaria) decumbens.
Toxic Plants of interest cause serious damage to livestock producers worldwide. In Brazil these plants also cause material losses to ranchers. Its
Keywords: Plant poisoning; Livestock; Semiarid; Epidemiology.; Planta tóxicas; Pecuária; Semi-árido; Epidemiologia; CIENCIAS AGRARIAS::MEDICINA VETERINARIA